Prevention of Narcotics Crime According to Islamic Law Perspective - Muhammad Ridha Haykal Amal (International Journal Reglement & Society (IJRS), 2020)
In the early days of Islam, there was no known narcotics as it is today, not even the Al-Qur'an or hadiths discussed the issue of narcotics. The explanation that is in the AlQuran and Hadith only matters of Khamr. However, narcotics is related to the word khamar because both have an impact, namely intoxication. In Islamic law there are sources of Islamic law, and one of the sources of Islamic law is by using the Kias method or it can be called legal analogy. Kias is an analogy of a problem where there is no legal stipulation (nash / argument) with a problem that already has a legal stipulation because of equality. The nature or danger caused by the misuse of narcotics is even more terrible than liquor or khamar, so the verses of the Koran that prohibit or prohibit liquor or khamar can be used as a basis or argument for the prohibition and prohibition of the use of narcotics. The procedure used to collect data in this study is documentation, namely the guidelines used in the form of notes or quotations, search for legal literature, books and others related to the identification of problems in this study both offline and online. Analysis of legal materials is carried out using the content analysis method (centent analysis method) which is carried out by describing the material of legal events or legal products in detail in order to facilitate interpretation in the discussion. The criminal act can be closely related to criminal law. Criminal law is a part of the legal system, because it contains sanctions. Therefore, a person who is convicted is a person who is guilty of violating a criminal law regulation or committing a criminal act or a crime. Law Number 35 of 2009 concerning Narcotics determines several narcotics crimes, namely in Article 111 to Article 148 of Law Number 35 of 2009 concerning Narcotics. Regarding how to prevent drugs in the perspective of Islamic law, the writer reveals several things, namely religious guidance (Da'wah Islamiyah). Regarding religious guidance (dakwah Islamiyah) on drug prevention, this should pay attention to several things. First, parties who handle religious guidance (Da'wah Islamiyah) should consist of various aspects of disciplines consisting of: ulama (kiyai / ustadz), psychologists, criminologists, psychiatrists, doctors, legal practitioners, sociology, security forces (police). and other parties involved in this drug problem